Analisis Perbandingan User Experience pada Aplikasi Gojek dan Maxim terhadap Mahasiswa Universitas IGM menggunakan Metode User Experience Questionnaire - Saputri, Nabila Dira; Kesuma, Hendra Di; Alie, M. Fadhiel (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Everything is changing with the transformation of the digital world, including app-based online motorcycle taxi services. These services have become a major innovation that simplifies users' transportation needs. In Indonesia, Gojek and Maxim are among the popular applications, including within the environment of Universitas Indo Global Mandiri (UIGM) Palembang. Their popularity has drawn attention to understanding the competition and the value they offer. Using the User Experience Questionnaire (UEQ) method, a comparison between Gojek and Maxim reveals the strengths and weaknesses of each. This method evaluates aspects such as attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. The UEQ questionnaire was distributed to 100 respondents. The analysis results showed that Gojek scored positively on 5 variables (attractiveness, perspicuity, efficiency, dependability, novelty) and neutral on 1 variable (stimulation). Meanwhile, Maxim scored positively on only 1 variable (perspicuity) and above average on 5 variables. The comparison indicates that Gojek significantly outperformed Maxim in 4 variables with higher average scores, making it superior in delivering a better user experience compared to Maxim.